2000
DOI: 10.1053/jfms.2000.0083
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sevoflurane in a 2:1 Mixture of Nitrous Oxide and Oxygen for Rapid Mask Induction of Anaesthesia in the Cat

Abstract: An inhalational technique for rapid induction of anaesthesia in unsedated cats using sevoflurane and nitrous oxide is described. Using a pliable, tight-fitting, face mask, sevoflurane (7.5-8%) was delivered from an out-of-circuit precision vaporiser connected to a coaxial non-rebreathing system using a fresh gas flow of 1 l oxygen and 2 l nitrous oxide per min. Cats were restrained with gentle but firm pressure applied by scruffing the dorsal cervical skin until the righting reflex was lost and the patient cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…This may be less of an issue for private practitioners conducting chemotherapy close to the owners place of residence, and where chemotherapy can be done at a more convenient time (such as weekends). Further, the ability to use sevoflurane 14 to immobilise cats rapidly and reversibly for chemotherapy has substantially improved the speed and readiness with which IV chemotherapy can be conducted; this may make the process of out-patient chemotherapy even more convenient for owners and the veterinary team. Overall, the results of the survey suggest that when confronted with a reasonably priced chemotherapy protocol, most well-motivated owners found the results of therapy rewarding, irrespective of the survival time of the individual cat.…”
Section: Aust Vet J Vol 79 No 12 December 2001mentioning
confidence: 99%
See 2 more Smart Citations
“…This may be less of an issue for private practitioners conducting chemotherapy close to the owners place of residence, and where chemotherapy can be done at a more convenient time (such as weekends). Further, the ability to use sevoflurane 14 to immobilise cats rapidly and reversibly for chemotherapy has substantially improved the speed and readiness with which IV chemotherapy can be conducted; this may make the process of out-patient chemotherapy even more convenient for owners and the veterinary team. Overall, the results of the survey suggest that when confronted with a reasonably priced chemotherapy protocol, most well-motivated owners found the results of therapy rewarding, irrespective of the survival time of the individual cat.…”
Section: Aust Vet J Vol 79 No 12 December 2001mentioning
confidence: 99%
“…Indeed, treatment of cats with LSA is considerably less expensive than treating dogs with LSA (especially large canine patients), as cytotoxic drugs are used in much smaller quantities. The recent decrease in the cost of doxorubicin 13 has further improved the affordability of multi-drug protocols incorporating this agent, while the availability of sevoflurane anaesthesia 14 to restrain temporarily cats during IV chemotherapy makes the mechanics of performing the procedure simpler, easier and quicker than in the past. Finally, recent detailed reports of survival times for North American cats treated with chemotherapy protocols are promising in terms of remission times, quality of life and the possibility of cure in a select proportion of cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like other inhalational agents, it produces a dose-dependent decrease in cardiac output, but at clinically effective concentrations cardiac output is well maintained (Doi andothers 1983, Hikasa andothers 1997). There is increasing interest in the use of sevoflurane in veterinary medicine (Branson and others 2001), and clinical trials have shown that this volatile anaesthetic agent is effective in cats and dogs (Tzannes andothers 2000, Branson andothers 2001).…”
mentioning
confidence: 99%
“…Για την εγκατάσταση της αναισθησίας στις γάτες έχει περιγραφεί η χρήση του σεβοφλουρανίου σε συνδυασμό με Ν 2 0, χωρίς την προηγουμένη εφαρμογή προαναισθη-τικής αγωγής, για την πραγματοποίηση συντόμων κλινι κών πράξεων (Tzannes et al 2000).…”
Section: γαταunclassified